At överskrida ras: En introduktion till begreppet transrasialitet speglad genom transrasiala erfarenheter och fantasier - Tobia Hübinette (The Royal Danish Library, 2011)
To transcend race: An introduction to the concept of transraciality seen through transracial experiences and fantasiesThis article introduces the concept of transraciality based on the following questions: Is it possible to transgress race in a similar way as it is possible to transgress sex? How does the transracial experience look like and how does it differ from a transracial fantasy? Who is transracial, and is it the same to transracialise from non-white to white as from white to non-white? The article takes up the experiences of non-white adoptees and their identifications of being white and of white people who want to become non-white both in a colonial and in a postcolonial setting, and argues that it is the non-white to white race transgression which has the potential to transform a dichotomous and hierarchical racial structure.